2018
DOI: 10.1002/er.3977
|View full text |Cite
|
Sign up to set email alerts
|

An investigational back surface cooling approach with different designs of heat-absorbing pipe for PV/T system

Abstract: Summary A solar photovoltaic panel accumulates substantial amount of heat, which deteriorates its performance. Thus, to minimize the panel temperature, 3 new designs (semioval serpentine, circular spiral, and circular spiral semiflattened) of absorbers for back surface cooling are introduced in this paper. Experimental investigations on the panel performances with and without the designed cooling systems are performed. A similar experiment with an existing serpentine design of absorbers is also conducted, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Bhattacharjeeetal. [12] performed experimental investigations using three different designs of solar photovoltaic panel (circular spiral, circular spiral semi-flattened, and semi-oval serpentine) to absorb heaton the back surface. The results showed that a circular spiral semi-flattened absorber most optimally performedamong all the investigated types because it showed highest efficiency (4.32%) and fill factor (19.80%).In a recent indoor study, Al-Waelietal.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharjeeetal. [12] performed experimental investigations using three different designs of solar photovoltaic panel (circular spiral, circular spiral semi-flattened, and semi-oval serpentine) to absorb heaton the back surface. The results showed that a circular spiral semi-flattened absorber most optimally performedamong all the investigated types because it showed highest efficiency (4.32%) and fill factor (19.80%).In a recent indoor study, Al-Waelietal.…”
Section: Introductionmentioning
confidence: 99%
“…By pointing the importance of PV surface temperature, Bhattacharjee et al presented three new designs to decrease the panel temperature for absorbers places on the back of the PV in their experimental research. They indicated that the circular spiral semiflattened design absorber has the best results for the PV cooling . Hader and Al‐Kouz focused on employing heat exchanger with attached fins to the parallel plates and water‐Al 2 O 3 nanofluid as a working fluid in their theoretical study …”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the circular spiral semiflattened design absorber has the best results for the PV cooling. 40 Hader and Al-Kouz focused on employing heat exchanger with attached fins to the parallel plates and water-Al 2 O 3 nanofluid as a working fluid in their theoretical study. 41 Related to the natural zeolites, there are a few studies on natural zeolites for solar energy in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The PV/T solar system was investigated by He et al where the influence of PV cell to thermal characteristics of the PV/T solar system was investigated. Bhattacharjee et al investigated the usage of heat‐absorbing pipe in a different design to cool the back surface of PV/T system.…”
Section: Introductionmentioning
confidence: 99%